The role of physical rehabilitation in patients after cardiac transplantation - V. V. Shapovalova; K. S. Feschuk (Ukrainian Journal of Cardiovascular Surgery, 2018)
Physical exercises are very important for treatment and rehabilitation measures on various stages of rehabilitation in patients after cardiac transplantation. Physical rehabilitation allows to prevent many postoperative complications, to increase the ability to adaption to the physical activities, that is, to improve the quality of life.